2019
DOI: 10.1007/s00217-019-03331-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the content of free phenolic acids and antioxidative capacity of wholemeal bread in relation to cereal species and fermentation type

Abstract: Only low molecular, simple phenolic acids and their dimers can be easily absorbed by intestinal cells. In this study, the changes in free (unbound) phenolic acids and antioxidative capacity were tracked from flour, through bread to final in vitro bread hydrolysate. The initial material of the study included wholemeal flours made of common wheat, spelt wheat and rye, fermented with baker's yeast Saccharomyces cerevisiae or by the use of baking starter made of lactic acid bacteria Lactobacillus casei and L. brev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 59 publications
3
24
0
Order By: Relevance
“…Among them, each single compound showed a significant increase, although at a different extent: within the main SPAs, sinapic acid showed a higher average increase (+ 15%) compared to ferulic acid (+ 6%), while among the minor compounds hydroxybenzoic and syringic acids increased by 35 and 24%, respectively. Our data are consistent with those reported by Skrajda-Brdak et al 43 , who observed that free benzoic acids were preferentially accumulated in yeast fermented breads. In addition, SPA increases in fermented dough were higher in cereals characterized by a greater wholegrain flour SPA content, in particular for emmer.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Among them, each single compound showed a significant increase, although at a different extent: within the main SPAs, sinapic acid showed a higher average increase (+ 15%) compared to ferulic acid (+ 6%), while among the minor compounds hydroxybenzoic and syringic acids increased by 35 and 24%, respectively. Our data are consistent with those reported by Skrajda-Brdak et al 43 , who observed that free benzoic acids were preferentially accumulated in yeast fermented breads. In addition, SPA increases in fermented dough were higher in cereals characterized by a greater wholegrain flour SPA content, in particular for emmer.…”
Section: Discussionsupporting
confidence: 94%
“…The 139 yeasts used in this study were maintained in the International Microbial Archives (IMA) of the Microbiology Labs of the Department of Agriculture, Food and Environment (DAFE) of the University of Pisa (Supplementary Table S3 online) and originated as follows: 78 strains were previously isolated from wheat Tuscan sourdoughs 19 , 3 S. cerevisiae strains from PDO Tuscan bread sourdough 27 . The other 58 yeasts were isolated from different Italian sourdoughs (43) and from Boza, a cereal-based fermented drink (15), following the method described in Palla et al 27 . Along with such isolates, two commercial baker's yeasts-S. cerevisiae Zeus IBA (ZEUS IBA srl) and S. cerevisiae Lievitalia (Lesaffre Italia spa)-and four reference strains ( Supplementary Table S3 online) were used.…”
Section: Methodsmentioning
confidence: 99%
“…The metabolic pathways (shikimate, phenylpropanoid) for their biosynthesis involve many biomolecules like acetyl CoA, malonyl CoA, pyruvate, acetate, and some amino acids (phenylalanine and tyrosine) [16]. Their beneficial properties in human health (anti-diabetic, anti-cancer, anti-inflammatory, anti-microbial, anti-oxidant, as well as neuro-, cardio-, and hepato-protective function) are attributed to their ideal chemical structure, which promotes electron transfer or hydrogen donation from the hydroxyl groups of their aromatic ring and thereby exhibit free radical scavenging activities and metal-chelating potential [60,62,63]. Phenolic components need to be in a soluble form to enter the human blood circulation system and bring about their antioxidant properties.…”
Section: Phenolic Componentsmentioning
confidence: 99%
“…Phenolic components need to be in a soluble form to enter the human blood circulation system and bring about their antioxidant properties. Phenolics in cereals can be found as free and soluble, conjugated and soluble (bound with sugars and sterols), and non-soluble, which are usually linked to polymers like arabinoxylans and lignin [63,64]. Increases of cereals' phenolic content can be achieved by size reduction of the particles, germination, addition of hydrolytic enzymes, and fermentation [63].…”
Section: Phenolic Componentsmentioning
confidence: 99%
See 1 more Smart Citation